The Influence of the Percentage of Poor Population and the Human Development Index on Gross Regional Domestic Product at Constant Prices in Dairi Regency, 2014–2025 - Epelima Sinaga; Mizael Demak Sitohang; Agnes Dea Lita Br Sitepu (International Journal For Advanced Research, 2026)
This study aims to examine the influence of the percentage of poor population and the Human Development Index (HDI) in Dairi Regency during the period 2014–2025. The research employs a quantitative approach using multiple linear regression analysis to analyze the relationship between independent and dependent variables. The study utilizes secondary data obtained from the Badan Pusat Statistik (BPS). The results of the analysis indicate that the percentage of poor population has a significant negative effect on Gross Regional Domestic Product at Constant Prices (GRDP-CP). In contrast, the Human Development Index shows a significant positive effect on GRDP-CP. Simultaneously, both variables are proven to have a significant influence and are able to explain a substantial proportion of the variation in GRDP-CP. These findings emphasize that poverty reduction and equitable access to development outcomes, particularly in the areas of education, health, and income, play an important role in supporting a more productive society and stimulating economic growth in Dairi Regency.